Biomechanical Reactions due to Orthodontic Forces. A Finite Element Study. (2015) - Bica, Cristina; Brezeanu, Ligia; Bica, Dorin; Suciu, Mircea
Abstract: The evaluation of biomechanical responses (displacements, stress) during the application of orthodontic forces in adult patients with alveolar bone resorption can be achieved through the implementation of computer-assisted biomechanical processes and phenomena. The purpose of this study was to quantify, using Finite Element Method (FEM), the biomechanical reactions with two components, displacements and stress, following the application of orthodontic pressure in the presence of a periodontal support with a gradual loss of the alveolar bone. ALGOR V16 software allowed us to achieve simulations with horizontal forces of progressively increasing intensity over the middle point of the vestibular side of the tooth. The effect of the forces was assessed by the values of stress and displacements on the alveolar bone. For the correct interpretation of the results, we traced the features of stress on both, oral and labial sides.